Reformulation of Regulation on Prostitution Crime as Predicate Crime in Money Laundering - Ardi Purboyo; Slamet Suhartono; Yovita Arie Mangesti (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2025)
Introduction: A person who carries out a financial transaction or other financial transaction that is suspected of hiding or disguising the origin of wealth from illegal acquisitions as if it were legitimate wealth and not the result of a crime, its truth must first be proven. Purposes of the Research: Research aims to find the urgency of regulating the crime of money laundering originating from prostitution in the National Criminal Code based on the principle of justice and the concept of reformulating the regulation of the crime of money laundering originating from prostitution in the National Criminal Code. Methods of the Research: A study uses normative legal research, namely legal research that focuses on the study, review, and analysis of positive law. This research is a review or analysis that focuses on the rules or provisions stipulated in applicable laws and regulations. A study was conducted on the primary legal materials and secondary legal materials used to answer the legal issues raised, namely related to the regulation of money laundering crimes originating from prostitution crimes. Results Main Findings of the Research: The results of the study show the urgency of reformulating the regulation of prostitution as a predicate crime in money laundering as a crime of follow does not reflect the value of justice for the community involved in both crimes. The concept of reformulating the regulation of prostitution as a predicate crime as a predicate crime in money laundering as a crime of follow must be classified against the perpetrators involved in prostitution activities. as a predicate crime in money laundering as a crime of follow must first be distinguished regarding the parties involved, such as pimps/intermediaries, providers of commercial sexual service facilities, and also sex workers who are distinguished as professions and sex workers as victims of sexual exploitation. The community understands that prostitution is not just a symptom of social pathology but is a criminal act. The community should be involved in social control efforts so that there are no further criminal acts, namely money laundering.